Implementation of proton therapy treatments with pencil beam scanning of targets with limited intrafraction motion. (January 2019) - Fracchiolla, Francesco; Dionisi, Francesco; Giacomelli, Irene; Hild, Sebastian; Esposito, Pier Giorgio; Lorentini, Stefano; Engwall, Erik; Amichetti, Maurizio; Schwarz, Marco
Highlights: We propose a workflow for the treatment of target with limited intrafraction motion. We present the application of the method on two patients treated for thymomas. We implemented a tool for the evaluation of the 4D dose evaluation of the plan and interplay effect assessment. Abstract: Purpose: To report on the implementation, validation and results of the first two proton therapy PBS treatments of limited amplitudes moving targets performed at our center. Methods and materials: A real time optical tracking system was used to monitor the patient surface during the CT scan and treatment. This system is also able to trigger the beam during the treatment. A 4DCT (10 phases) and a Free-Breathing CT (FBCT) were used for the planning. The physician used the 4DCT for ITV delineation, while planning was performed on the FBCT. The approved plan was evaluated in two ways: - dose recalculation on each 4DCT phase. - Interplay effect evaluation: every spot was assigned to a phase according to the beam delivery time and the breathing curve of the patient. The 10 doses were then deformed and summed on the FBCT. The largest breathing amplitude recorded during 4DCT scan was used as gating safety threshold during treatment delivery. This planning and treatment workflow was then applied for two patients affected by thoracic thymoma. Results: The dosimetric evaluation of the plan showed no interplay effect. The second patient showed an overdosage to the coronary and Left Anterior Descending area in the worst case scenario but it was below the constraints. Duty Cycle together with number of beam interruptions gave information about the patient compliance to the treatment: the first patient breath is stable and within thresholds, whilst the second patient had more variations, causing multiple beam interruptions. Conclusion: We defined and used for two patients a protocol for the treatment of small amplitude moving targets. The planning and delivery of the treatments gave very good results in terms of coverage, OARs sparing, 4D dose evaluation of the plan and interplay effect assessment.